677.21 WAYS TO IMPROVE THE EFFICIENCY OF MOVING DEVICE USED IN AIR TRANSPORTATION OF COTTON: Pneumotransportation - Salokhiddinova, Makhliyo; Muradov, Rustam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article analyzes the problems of increasing the efficiency of the propulsion device used at cotton ginning enterprises for transporting cotton by air. The work process, disadvantages and advantages of currently used types of pneumatic transport in stationary and mobile conditions have been studied. Based on the results of the analysis, a new design of the drive device was proposed. The operating procedure of the improved version of the propulsion system is also described in detail. By implementing the proposed design, it is possible to maintain the original quality indicators of raw materials during primary processing at cotton ginning enterprises, as well as to prevent the combination of free fibers with waste and air-absorbed dust.